ANALISIS DAMPAK ALOKASI DANA DESA (ADD) TERHADAP PEMBERDAYAAN MASYARAKAT DAN KELEMBAGAAN DESA - Mahfudz, Mahfudz (LPPM Universitas Terbuka, 2009)
This research has aim to analyze the effectiveness of allocation, management and using of village-fund-allocation (ADD) in ?X? Regency and analyze the impact of ADD toward the improvement of public infrastructure, manpower absorption as well as the empowerment of people and village institutions. The research was performed in 18 sub-districts, in which on every sub-district two villages are chosen, that is one village classified as ?urban village? that located near the sub-district capital and other village classified as ?rural village? that is a village categorized as isolated. Meanwhile as respondents of research on every village are boards of village institutions: board of village representatives board (BPD), board of village community defense board (LKMD), board of neighbourhood organization (RT), board of family welfare empowerment (PKK), board of youth organization (Karang Taruna), and board of civil defense taskforce (Satgas Hansip) ? each of them represented by one person. Thus, totally for entire research field (?X? Regency) there are 216 respondents. Collection of secondary and primary data performed through survey on site using questionnaire. Result of research shows that many regulation regarding ADD are not well implemented according to the existing laws. A large part of people more prefer to ADD with different amount for each village considering some factors such as the number of people, village accessibility, potential owned by each village, etc. However, the majority of people consider that ADD has positive impact and multiplier effect significantly for them such as the improvement of public infrastructure, improvement of people?s knowledge, the increasing of people participation in village development and manpower absorption